A Conceptual Critique of “Oil, State, and Industrialization in Iran”: An Unsuccessful Narrative of Industrial Policy-making in Iran Policy-making in Iran - Masoud Darroudi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The reason for non-development in the Iranian society is one of the important concepts with which Iranian thinkers have dealt in the last hundred years. It has been examined from different perspectives. The policy-making for industrial development which was pursued since Reza Shah’s government in order to reconstruct the substructures of Iran, is one of the most important phenomena for the study of non-development. Although the study and examination of reasons of industrial development are very crucial in this regard, few works have dealt with the reasons for industrial non-development. The book “Oil, State, and Industrialization in Iran” by Massoud Karshenas (Professor at SOAS University of London) is one of the few works which deal with the reasons for inefficient industrial policy-making in Iran. Karshenas tries to study the effects of oil on the industrial policy-making in Pahlavi era with a structural approach. This article provides a critique of his approach towards the effects of oil on the industrial industrialization and its implications.